Editorial – “Together We Build Our Health”: Paving Way Forward Through Analyzing the Context and Ensuring Wide Participation in the First and Second Health Forums in Sudan - Dafalla, Faihaa; Awadalla, Heitham; Husain, Nazik Elmalaika (Sudan Journal of Medical Sciences, 2022)
This is an Editorial and does not have an abstract. Please download the PDF or view the article HTML.